Numerical Simulation of Supersonic Carman Curve Bodies with Aerospike - HaiLong Zhao; Ke Peng; ZePing Wu; WeiHua Zhang; JiaWei Yang; JingBo Sun (International Journal of Aerospace Engineering)
Drag reduction is one of the important problems for the supersonic vehicles. As one of the drag reduction methods, aerospike has been used in some equipment because of its good drag reduction effect. In this paper, the numerical simulations of Carman curve bodies with different lengths of the aerospike and different radius of the flat cylindrical aerodisk in supersonic flow freestream are investigated. Based on the numerical simulations, the mechanism of drag reduction of the aerospike is discussed. The drag reduction effect influence of the parameters of the aerodisk radius and the aerospike length on the Carman curve body is analyzed. The aerodisk radius within a certain range is helpful for the drag reduction. The change of length of the aerospike has little effect on the drag of Carmen curve bodies. The drag reduction effect of the same aerospike becomes worse with the increase of the incoming Mach number.